The impact of vowels at the morphological level - bendadache, mohammed; lousra, mohamed (El Omda in Linguistics and Discourse Analysis, 2024)
This search presents the study of Arabic linguistic phonemes (sounds) named as (vowels and long vowels) and identifying the connection (relations hip) between the morphological lesson and vowel sounds through highlighting the linguistic function performed by the vowels in forming and diversifying morphological forms whether they are nominal or verbal and the resulting change diversity in meaning and morphological significance of the word IL also aims to the importance of the vocal relations that occur between the sounds within the phonetic context as it used in expressing more morphological issues such as : assimilation- snoring- Substitution -Transferring